The relationship between glaucoma and dry eye illness as well as the function of preservatives in glaucoma drugs - Lakra, Marianus Deepak; Kumari, Puspa; Murmu, Sarojini (International Journal of Research in Medical Sciences, 2023)
Background: The aim of the study was to evaluate the incidence of xerophthalmia in individuals with glaucoma by administering a topical regimen of antiglaucoma medication containing timolol and dorzolamide and to determine the frequency of ocular surface abnormalities among individuals with glaucoma who are undergoing treatment with topical antiglaucoma medications. Methods: The study included a total of 75 participants of both genders. A total of 50 ocular units from 25 subjects under medication with two or more antiglaucoma agents for a period of six months were subjected to examination. Results: The study compared tear breakage time, Schirmer’s test-1, and corneal staining score between the glaucoma cases and control groups. The mean values for tear breakage time were 9.44±2.76 seconds and 11.8±1.88 sec in the glaucoma and control group respectively (p=0.001). The mean values for Schirmer’s test-1 were 7.63±2.64 mm and 12.86±1.93 mm in the glaucoma and control group respectively (p=0.001). The mean values for corneal staining score were 5.7±2.33 and 1.1±0.58 in the glaucoma and control group (p=0.001) respectively. Conclusions: The prevalence of ocular surface disease and dry eye is higher among individuals undergoing antiglaucoma therapy. The application of glaucoma medication in the form of topical treatment has been associated with the development of dry eye syndrome and has been observed to affect the stability of the tear film.